Figur Ular Pada Prasasti Telaga Batu: Upaya Pemaknaan Berdasarkan Pendekatan Semiotika Peirce - Muhamad Alnoza (Balai Arkeologi Yogyakarta, 2020)
Sriwijaya is a kingdom that developed between the 7th and 11th centuries AD. The inscriptions become archaeological remains as well as written sources that can reconstruct Sriwijaya's cultural history. The Telaga Batu inscription as one of Sriwijaya inscriptions is different from other inscriptions because it has the only ornament in living creature shape and it is the longest inscription among the others. The ornaments found on the Telaga Batu Inscription are in the form of a seven-headed snake. This study attempts to answer the meaning of the seven-headed snake figure with Peirce's triadic semiotic method. In answering these questions, a series of stages of archaeological research are used, including data collection, data analysis and interpretation. The snake figure in the Telaga Batu inscription can eventually be interpreted as a manifestation of the Datu's protector and the form of the Datu as a Buddha.